2022
DOI: 10.3389/fmed.2022.909982
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Nausea and Vomiting in Female Patients Undergoing Breast and Gynecological Surgery: A Narrative Review of Risk Factors and Prophylaxis

Abstract: Postoperative nausea and vomiting (PONV) have been widely studied as a multifactorial entity, being of female gender the strongest risk factor. Reported PONV incidence in female surgical populations is extremely variable among randomized clinical trials. In this narrative review, we intend to summarize the incidence, independent predictors, pharmacological and non-pharmacological interventions for PONV reported in recently published clinical trials carried out in female patients undergoing breast and gynecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…4 The current published articles dealing with the issue of postoperative vomiting and nausea in women undergoing gynecological operations are extremely inconsistent concerning management, prediction, incidence, and risk factors. 8 ondansetron groups (P < 0.05). The rate of nausea in combined group was significantly lower than that of dexamethasone and ondansetron groups.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…4 The current published articles dealing with the issue of postoperative vomiting and nausea in women undergoing gynecological operations are extremely inconsistent concerning management, prediction, incidence, and risk factors. 8 ondansetron groups (P < 0.05). The rate of nausea in combined group was significantly lower than that of dexamethasone and ondansetron groups.…”
Section: Introductionmentioning
confidence: 91%
“…4,7 Gynecological and obstetrical operations are among the most frequent types of surgeries associated with nausea and vomiting postoperatively. 8 Nausea and vomiting occur in about 80-95% of women who are administered low dose of prophylactic antiemetic medication within the first 24 h following surgery. 8,9 It has been shown that female gender and gynecological operations are among the strong predictors of postoperative vomiting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Female sex was an independent risk factor for PONV, and carbon dioxide pneumoperitoneum and Trendelenburg positioning were risk factors for PONV in gynaecological surgery; therefore, the incidence of PONV in gynaecological surgery was high in this study. (Echeverria-Villalobos et al, 2022).…”
Section: Comparison Of Anaesthesia-related Outcomes In Patients Monit...mentioning
confidence: 99%